Biodiversity and ecological economics participation, values and resource management - Tacconi, Luca (London Earthscan, 2000)
Biodiversity and ecological economics is a model of applied ecological economics.It presents an accessible introduction to the subjects while at the same time broadening its theoretical basis by introducing a post-positivist,participatory methods.The theo
Keywords: Environmental economics; Ecology-Economic aspects; Economic of natural resources-Economic aspects; Biological doversity conservation; Ecology-Economic aspects-Case studies; Biological diversity-Conservation-Case studies